-2
$\begingroup$

I'm self-studying from Stroud & Booth's amazing "Engineering Mathematics", but am stuck on a problem from the "Partial Fractions" chapter.

I've been running around in circles trying to solve it, and just can't seem to get it right (although I understand the general mechanics around the solution process).

The expression that I need to split into partial fractions is:

$$\frac{9x^2+48x+18}{(2x+1)(x^2+8x+3)}$$

Can anyone please help me out?

$\endgroup$
  • 14
    $\begingroup$ This is not an equation. $\endgroup$ – Dietrich Burde May 25 at 16:02
  • 1
    $\begingroup$ An equation "equates" a (left hand side) LHS to a RHS with an equal sign. $\endgroup$ – Jean Marie May 25 at 16:20
  • $\begingroup$ I think neuron wants to find the partial fractions as he has stated in the body of the question, probably misunderstood about equation $\endgroup$ – Ak19 May 25 at 16:23
0
$\begingroup$

(Assuming you want to split it into partial fractions)

Let $$\frac{9x^2+48x+18}{(2x+1)(x^2+8x+3)} = \frac{a}{2x+1} + \frac{bx+c}{x^2+8x+3}$$

By inspection,

At $x=-\frac{1}{2}$,

$$\frac{9/4-48/2+18}{1/4-8/2+3} = a\implies a = 5$$

At $x=0$

$$\frac{0+0+18}{(0+1)(0+0+3)} = \frac{5}{0+1}+\frac{c}{0+0+3}\implies c =3 $$

At $x=1$

$$\frac{9+48+18}{3(1+8+3)} = \frac{5}{3}+\frac{b+3}{1+8+3}\implies b=2$$

So, $$\frac{9x^2+48x+18}{(2x+1)(x^2+8x+3)} = \frac{5}{2x+1} + \frac{2x+3}{x^2+8x+3}$$

$\endgroup$
  • $\begingroup$ You should explain how you know the thing has a partial fractions expansion of that form! $\endgroup$ – David C. Ullrich May 25 at 18:00
  • $\begingroup$ For example, $\frac{x}{(x-1)(x^2-1)}=\frac a{x-1}+\frac{bx+c}{x^2-1}$ will not work... $\endgroup$ – David C. Ullrich May 25 at 18:03

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.